PTU-071 A nurse led day case paracentesis service in a district general hospital saves bed days. (17th June 2017) - Wilkinson, D; Jones, J; Bassi, A; McLindon, J; Dobson, J; Fox, M; Theis, V; Chandy, R; Priestley, S; McClements, D
Abstract : Introduction: Some patients who have stable cirrhosis require regular therapeutic paracentesis. In our hospital these patients would be admitted directly to the Gastroenterology ward for treatment. Given the pressure on inpatient beds we established a nurse led treatment unit on the Gastroenterology ward to avoid admissions and improve efficiency. Method: A ward administrative area was converted into a day unit containing two trolley beds. A paracentesis pathway including competency based training was developed and a band 6 specialist nurse position was established. Between May 2016 and December 2016 data was prospectively collected for all day case paracentesis procedures including demographics, length of stay, volume of ascites drained and complications. A retrospective review of electronic patient records was performed to calculate the length of stay (LoS) for those patients who had been previously admitted for elective paracentesis prior to the initiation of the nurse led service. National data for cost per bed day was used to estimate cost savings. Results: Fifty six day case paracentesis procedures were performed in the nurse led treatment unit between May 2016 and December 2016. Male:Female ratio was 54:2, mean age was 52 (range ). The mean volume drained was 9100mls (range 1, 600–20 200, 200mls). 54 (96%) of patient were discharged the same day following paracentesis. Two patients were admitted to the Gastroenterology ward, 1 patient was diagnosed with spontaneous bacterial peritonitis, 1 patient was found to have renal dysfunction. Mean LoS for patients admitted for elective therapeutic paracentesis was 4 days. We calculate that the nurse led treatment unit has saved 216 bed days. Assuming a cost of £400/bed day 1 this equates to a cost saving of £86 400 over a 9 month period. Conclusion: A protocol driven, nurse led day case paracentesis service is safe, avoids hospital admissions, reduces demand on inpatient beds and saves money. This model of care is easy to establish, requires minimal investment and can have a significant impact in reducing bed days. We plan to expand the treatments offered in the nurse led treatment unit to support new ambulatory treatment pathways. Reference: . Department of Health (2015). Data Requests: NHS Hospital Stay. Available at: https://data.gov.uk/data-request/nhs-hospital-stay. [Accessed 24th Feb 2017]. Disclosure of Interest: None Declared